Ecological Study of Bidens pilosa in Bandung, West Java, Indonesia - Oktaviant, Dimas Panji; Rosleine, Dian (Journal of Tropical Biodiversity and Biotechnology, 2024)
Bidens pilosa has been widely distributed from tropical to temperate regions and is often reported as a weed in agriculture. It readily thrives in various environments, naturally spreading to open areas and artificial ecosystems, establishing new populations, emphasising the need for ecological studies to prevent its invasive potential. In this study, we focused on population study of B. pilosa and its distribution in Bandung as urban area. Survey was conducted using 1x1 m quadrate plots in eight locations (24 plots). Individual number of B. pilosa, the number of flowers in each individual, coordinates, and altitude of each plot were recorded to describe population structure and map this population in Bandung. Air temperature (°C), humidity (%), light intensity (Lux), and soil water content (%) were measured. Individual number and environmental condition are analysed using cluster analysis and PCA, then mapped using IDW (Inverse Distance Weighting). The highest population in AR (652 ind), followed by CG (626 ind), TR (253 ind), PA (135 ind), CW (78 ind), NR (39 ind), PU (28 ind), and PR (20 ind). On average, each B. pilosa individual produces 61 inflorescences, indicating a mature population with all developmental stages present across all locations. Ordination plots shows that B. pilosa has wide range of environmental condition from open to shade area with various environmental condition. Open areas, settlements, and agriculture host dense B. pilosa populations, and its biological traits suggest it may become invasive without proper control.